The relationship between identification and loyalty in a public university: Are there differences between (the perceptions) professors and graduates? - Gabriel Cachón Rodríguez; Camilo Prado Román; José Ángel Zúñiga-Vicente (European Research on Management and Business Economics, 2019)
This study analyses the relationship between identification and loyalty and also compares the perceptions of two groups of key stakeholders (professors and graduates) of a public institution of higher education, as mechanisms to gain competitiveness against private institutions. To carry out this research, an on-line survey was conducted and the results were analyzed through a system of structural equations using the partial least squares technique (PLS-SEM). The results reveal that identification influences loyalty, and that there are also significant differences in the perception between professors and graduates, being the relationship between identification and loyalty more intense in the former group than the latter. Several significant implications can be derived from our research for the management of higher education institutions. JEL classification: M31, M21, A22, Keywords: Identification, Loyalty, Higher education